PROJECT METHOD AS A MEANS OF ACTIVATING STUDENTS 'Cognitive ACTIVITIES - Сілакова, Т. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article analyzes the directions of using project technologies for activation of students' cognitive activity. The principles of application of project technologies as an effective complement to other pedagogical technologies that contribute to the development of the student's personality as a subject of activity and social relations are considered. The list of students' personal development skills in the process of project activity and the basic requirements for the use of project-based learning technologies are given. The system of actions of the teacher and students at different stages of project work and the skills required in the conditions of updating the educational process of the modern higher education are given. It is established that the use of project technologies in the practice of higher education will allow to form the competences of students, which allow to determine the student's readiness for life, his further personal development and for active participation in the life of society. The basic principle of the project method is that the starting point of learning should be the student interests of today. The article also examines a retrospective analysis of the formation and development of project technology of teaching in foreign pedagogy of the XX century, which made it possible to draw conclusions about the tendency of its development and essential characteristics. It is concluded that project technology is an important tool for problematic learning and is a reflection of the research method of teaching, the project method is one of innovative pedagogical technologies that meets the requirements of the National Doctrine of Educational Development on the transition to a new type of humanistic-innovative education, when attention is transferred to the process gaining students knowledge, skills, life experiences that transform into competencies